Static in the system : noise and the soundscape of American cinema culture - Ward, Meredith C., 1981- (Oakland, California : University of California Press, 2019)
"Static in the System analyzes the relationship between American aural cultural history and cinema. Focusing specifically on the field of cinema culture--the envelope that surrounds and conditions our experience of cinema as an art form--Meredith C. Ward discusses how the aural culture of a given time period has enabled certain types of listening cultures to form. Analyzing which forms of listening have been dominant in various periods, she also discusses how noise--that commonly used but little-understood term--helps us to make sense of the ongoing conflicts underlying these moments, and where we have, historically, set the limits of 'desirable' and 'undesirable' sound"--Provided by publisher.
Introduction : noise and the concept of the cinema soundscape -- Songs of the sonic body : noise and the sounds of early motion picture audiences -- The film industry lays the golden egg : noise, electro-acoustics, and the academy's adjustment to film sound -- "Machines for listening" : cinema auditoriums as vehicles for aural absorption -- Cinema theaters as antiquated as "Edison and his wax cylinders" : mobile technologies and the negotiation of public noise -- Conclusion : noises we will be hearing soon.
Includes bibliographical references and index.
Online resource; title from digital title page (viewed on November 05, 2019).
In English.
eBooks on EBSCOhost
Keywords: Motion picture theaters -- United States; Noise; Motion picture audiences -- United States; Noise; Cinéma -- Publics -- États-Unis.; Bruit; noise; PERFORMING ARTS -- Reference; MUSIC -- History & Criticism; Motion picture audiences; Motion picture theaters; Noise; United States; america; american culture; architectural acoustics; aural cultural history; avoidance of noise; built environment; cinema theatres; cinema; class; electro acoustics; film going culture; film sound; gender; history of noise; industry; listening cultures; mobile listening; motion picture history; movies; noise manifestations; sexuality; social power; sonic culture; sound theory; soundscape; theories of power; urban environment